2003
DOI: 10.1109/tnsre.2003.817674
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of muscle disuse atrophy by low-frequency electrical stimulation in rats

Abstract: When muscles lose neural drive, they atrophy rapidly. Neuromuscular electrical stimulation (NMS) has been used in attempts to prevent or reverse the atrophy, but optimal stimulation programs and parameters are not well defined. In this study, we investigated the effects of four different stimulation patterns on disuse atrophy produced in the tibialis anterior, lateral gastrocnemius, and soleus muscles of rats paralyzed with tetrodotoxin for seven days. Stimulation paradigms differed from one another by their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 35 publications
(58 reference statements)
1
20
0
Order By: Relevance
“…Electrical stimulation has been explored as a means of counteracting skeletal muscle atrophy in various clinical conditions, such as spinal cord injury [14], aging [15], spaceflight [16], and disuse [17], [18]. The effect of electrical stimulation depends on the atrophy model and the parameters of electrical stimulation, particularly the frequency and duration of stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical stimulation has been explored as a means of counteracting skeletal muscle atrophy in various clinical conditions, such as spinal cord injury [14], aging [15], spaceflight [16], and disuse [17], [18]. The effect of electrical stimulation depends on the atrophy model and the parameters of electrical stimulation, particularly the frequency and duration of stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of electrical stimulation depends on the atrophy model and the parameters of electrical stimulation, particularly the frequency and duration of stimulation. Low-frequency stimulation (2–20 Hz) that matches the motor unit firing pattern of a slow-twitch muscle, such as the soleus muscle, has been shown to be effective in attenuating disuse muscle atrophy [17], although the underlying mechanisms are far from clear. We have previously demonstrated that, during hindlimb suspension, application of low-frequency electrical stimulation at 20 Hz on the soleus muscles with defined timing and pulse parameters partially rescued the loss of satellite cells and improved fiber cross-sectional areas [19].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of electrical stimulation (ES) in counteracting muscle atrophy has been described in various clinical conditions such as disuse [14], aging [15], spinal cord injury [16], and space flight [17]. Because the atrophic response to disuse is usually greater in the slow-twitch soleus muscles [6,10,18], low frequency (2-20 Hz) pattern of stimulation that matches the muscle properties and the motor unit firing pattern has been shown to be effective in preventing disuse muscle atrophy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the pulse of low frequency electric stimulation for spasmodic muscle could lower muscular tension and most patients were reported to have spasm relieved within 6–14 h after treatment (19,20). …”
Section: Introductionmentioning
confidence: 99%